Perception of Science Teacher Candidates Towards Cultural Literacy - M. Khairul Wazni; Agus Muliadi; Sarwati Sarwati (Postgraduate, University of Mataram, 2023)
This study aims to describing the perception of science teacher candidates toward cultural literacy. This study is an exploratory research with 61 biology education students as subjects, comprising 28 from the Biology Education program at Mandalika University of Education, 16 from Hamzanwadi University, and 17 from Mataram State Islamic University. The research instrument used was a closed questionnaire with degraded answers according to a Likert scale that had been declared valid. Analysis of research data used is descriptive statistics and inferential statistics with Anova test at a significance level of 5%. The results of the study show that (1) average score of student perceptions regarding cultural literacy, namely, students from Mandalika University of Education have an average score of 2.86 in the Good category, students from Hamzanwadi University have an average score of 2.58 in the Good category, and students from Mataram State Islamic University have an average score of 2.64 in the Good category.; (2) there is a significant difference in the perception of students at Mandalika University of Education, Hamzanwadi University, and Mataram State Islamic University regarding cultural literacy, as evidenced by a significance value of 0.030 is smaller than the alpha testing value of 0.05 (<0.05).